Estudo comparativo de soldagem entre os processos TIG automatizado e o processo TIG manual na fabricação de tanques com espessura de chapa reduzida - Cherubim, Sandro (Universidade Federal de São Carlos, 2024)
Automation in welding processes has been growing since the 1970s. The technical benefits, when compared to the manual welding process, are numerous: productivity, quality, operator safety, and other things. This project addresses TIG welding (Tungsten Inert Gas), also known as GTAW (Gas Tungsten Arc Welding), developed between the late 1930s and the early 1940s, during a period of significant industrial and technological transformation driven by World War II. This historical context was marked by an intense demand for new manufacturing processes, especially to meet the needs of the growing aeronautical and military industries, which required more sophisticated and precise welding methods. Currently, this process is of utmost importance in the manufacturing and maintenance of parts in different sectors, such as automotive, railway, aerospace, civil, among others. The advantage of TIG welding includes the high quality of the welds produced, the possibility of joining different materials, and dimensional precision. The general objective of this work was to develop a study to verify the feasibility of the automated (orbital) TIG welding process, in relation to the manual TIG process, applied in the production of water reservoirs in AISI 304 stainless steel. The reservoirs are part of solar heating systems and are designed to have sheets up to 2 mm thick. The established method was to compare the appearance, structure, and functionality of the weld beads through visual analysis, tensile mechanical testing, liquid penetrant testing, and magnetic particle testing. The study used samples taken from water reservoirs (body and lid) made of AISI 304 stainless steel. The tensile mechanical tests demonstrated that the automated welds had moderate results, with 7 out of 12 test specimens breaking in the base material instead of the weld, indicating that the weld was not the weakest point. The stress versus strain graphs, comparing the manual and automated processes, indicate that the base material has a tensile strength between 600 and 675 MPa, with a deformation of 0.6 to 0.7. The automated weld, on the other hand, exhibited higher tensile strength, between 800 and 900 MPa, but with lower deformation (0.3 to 0.4). The results of the Liquid Penetrant and Magnetic Particle tests revealed discontinuities in both manual and automated welds, suggesting the need for improvements in the sheet preparation process. The design and construction of an automated orbital TIG welding machine was primarily motivated by the increase in productivity, with a 25% improvement in speed compared to the manual process. This increase in speed impacts quality factors, such as weld penetration, highlighting that the automated process is viable but still requires improvements.
Comparative study of welding between the automated TIG process and the manual TIG process in the manufacturing of tanks with reduced sheet thickness
Keywords: Processo TIG; Soldagem manual; Soldagem automatizada; Aços inoxidáveis; Ensaios destrutivos; Ensaios não destrutivos; TIG process; Manual welding; Automated welding; Stainless steels; Destructive testing; Non-destructive testing; ENGENHARIAS::ENGENHARIA MECANICA